Data collection for attack detection and security measurement in Mobile Ad Hoc Networks: A survey. (1st March 2018) - Liu, Gao; Yan, Zheng; Pedrycz, Witold
Abstract: Mobile Ad Hoc Network (MANET) is becoming one type of major next generation wireless networks. Nevertheless, it easily suffers from various attacks due to its specific characteristics. In order to evaluate and measure the security of MANET in real time and make this network react accordingly, a promising alternative is to integrate detection mechanisms that play a role of the second line of defense to detect attacks in MANETs. We note that in most attack detection mechanisms, it is essential and crucial to collect the data related to security for further analysis. If security-related data collection is untrustworthy, attack detection and security measurement might be impacted and disabled. Unfortunately, few existing studies concern security-related data collection in attack detection for the purpose of trustworthy security measurement. The literature lacks a thorough survey on security-related data collection for attack detection and security measurement in MANETs. In this paper, we propose a number of requirements for trustworthy security-related data collection, and then review detection mechanisms in MANETs that were published in recent 20 years. In particular, we employ the proposed requirements as a set of criteria to evaluate the existing work about security-related data collection. Based on the survey and evaluation, we identify a number of open issues and point out future research directions. Highlights: Specify requirements of security-related data collection. Provide a holistic summary on the main attacks in MANETs. Perform a thorough review on attack detection in MANETs. Summarize the types of security-related data for attack detection. Identify a number of open issues by employing the proposed requirements.